Balança de Ampère-Faraday: uma estratégia para discutir campo magnético e força magnética - Fernandes, José Amilton (2015)
This work is the result of a research aimed at basic education, developed under the National Professional Master’s program in Physics Teaching – MNPEF, held at Federal University of Lavras – UFLA from August 2013 to August 2015. It was conceived to motivate and make physics significant to secondary school students by considering a strategy to discuss the magnetic field and magnetic force. It is described a didactic sequence for teaching and learning in an experimental problem context. The design and development of a prototype set for measuring the magnetic force on a wire carrying an electric current in the presence of an external magnetic field using an digital mini-scale is presented. It is also discussed the underlying physical concepts and the different sets tested, as well as the source of spurious effects that might hinder the understanding of the subject. It is proposed a didactic transposition strategy to foster a conceptual inquire by the student triggered by cognitive conflict. The following topics are discussed: the learning theory on which this work is based, the methods used in the teaching sequence and for obtaining the results and their evaluation. The major output is an educational product for schools comprehending a list of activities, a guidance for the teacher, and a manual to build the prototype. The proposed activities were tested in a 3rd year high school class with 40 students at the beginning of an electromagnetism course held at State School Mayor Celso Vieira Vilela in Heliodora, Minas Gerais State.